A randomized pilot study of the use of concept maps to enhance problem-based learning among first-year medical students. (25th April 2013) - Veronese, Carolina; Richards, Jeremy B.; Pernar, Luise; Sullivan, Amy M.; Schwartzstein, Richard M.
Abstract : Background : Medical student education is challenging, and concept maps (CMs) can help students link new and existing knowledge, promote critical thinking and identify knowledge gaps. Aims : To study the feasibility, acceptability, and effectiveness of CMs in problem-based learning (PBL) tutorials. Method : Students and tutors were randomized to tutorials that used or did not use CMs. A mixed-methods approach generated qualitative and quantitative results of participants' perspectives on and the effects of CMs in PBL tutorials. Results : Student survey response rate was 71% (122/172). Most students (82.6%) planned to use CMs in the future at least occasionally, and students in CM tutorials endorsed increased likelihood of using CMs in the future ( p  = 0.02) versus students in non-CM tutorials. Qualitative analyses identified consistent associations between CMs and recurrent themes: integration of physiological mechanisms, challenging students' knowledge of the material, and identification of knowledge gaps. Quantitative assessment of final exam scores revealed a statistically significant increase in the students' scores in CM tutorials versus students in non-CM tutorials with an a priori α of <0.10. Conclusions : CMs are well accepted by students and faculty, feasible to incorporate into PBL tutorials, and may result in improved exam performance and student learning of physiologic concepts.